Oxygen permeation mechanism in polycrystalline mullite at high temperatures. Issue 7 (3rd April 2017) - Kitaoka, Satoshi; Matsudaira, Tsuneaki; Yokoe, Daisuke; Kato, Takeharu; Takata, Masasuke
Abstract: The oxygen permeability of polycrystalline mullite wafers, serving as a model environmental barrier coating layer on SiC fiber‐reinforced SiC matrix composites, was evaluated at temperatures above 1673 h with an oxygen tracer gas ( 18 O2 ). Oxygen permeation occurred by grain‐boundary (GB) diffusion of oxygen from the high oxygen partial pressure (high‐ P o 2 ) surface to the low‐ P o 2 surface, with simultaneous GB diffusion of aluminum in the opposite direction. This GB interdiffusion of both oxygen and aluminum proceeded without acceleration or retardation, maintaining the Gibbs‐Duhem relationship. Oxygen permeation related to the GB diffusion of silicon was negligibly small compared to that generated by aluminum GB diffusion, resulting in decomposition of the mullite near the low‐ P o 2 surface. The GB diffusion coefficients for oxygen in the vicinity of the high‐ P o 2 surface were determined directly from the SIMS‐ 18 O line profiles along individual GBs, as assessed from cross sections of the exposed wafer. The coefficients thus obtained were comparable to those determined in the absence of an oxygen potential gradient and those calculated from an oxygen permeation trial under the assumption of nearly ionic conductivity.